Multi-purpose community centres : a local economic development strategy towards sustainable community empowerment and poverty alleviation in the Dwars River region - Bruiners, Natasja (Stellenbosch : Stellenbosch University, 2012)
Thesis (MS en S)--Stellenbosch University, 2003.